Nursing of a patient with gastroparesis syndrome after gastrectomy for gastric cancer treated with Traditional Chinese Medicine ointment massage and acupoint application (中药膏摩联合穴位贴敷治疗1例胃癌术后并发胃瘫综合征患者的护理体会) - ZHAO Baoya (赵保亚); ZHANG Lei (张蕾); LIU Shuhong (刘书红); ZHAO Yan (赵燕) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the nursing management for a patient with gastroparesis syndrome after gastrectomy for gastric cancer treated with Traditional Chinese Medicine (TCM) ointment massage and acupoint application. TCM herbs for making ointment and related acupoints were selected based on the syndrome differentiation. The TCM ointment massage and acupoint application was carried out to relieve the symptoms of gastroparesis after gastrectomy and improve the recovery of gastrointestinal function. (本文总结1例胃癌术后并发胃瘫综合征患者实施中医外治法干预的护理体验。基于中医辨证分型, 选取中药组方和相关穴位, 开展中药膏摩和穴位贴敷, 可有效改善胃癌术后并发胃瘫综合征患者不适症状, 促进患者胃肠功能恢复。)